1983
DOI: 10.1021/es00112a010
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of cadmium toxicity toward the alga Selenastrum capricornutum Printz in two lakes with different humus content

Abstract: The alga Selenastrum capricornutum Printz is used to investigate the potential of natural lake water to reduce cadmium toxicity. The two lakes involved differ in trophic status and in concentration and composition of dissolved organic matter, one being a typical dystrophic bog lake, the other a less humus influenced, eutrophic lake. In the dystrophic lake, the toxic effect is determined mainly by the free cadmium activity. In the eutrophic, less humus influenced lake, however, the toxic effect shows considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 14 publications
(14 reference statements)
1
9
0
1
Order By: Relevance
“…Ogiwara and Kodaira (1989) support this finding with data showing that the stability constant for the DOC-copper complex was 10 times higher during the growth phase than that occurring after the population crash. In contrast, Laegreid et al (1983) observed higher cadmium toxicity during the growth sea-son, which they attributed to qualitative differences in DOC.…”
Section: Algal Biomass Doc and Ph Effects On Ionic Copper And Toxicitysupporting
confidence: 63%
See 1 more Smart Citation
“…Ogiwara and Kodaira (1989) support this finding with data showing that the stability constant for the DOC-copper complex was 10 times higher during the growth phase than that occurring after the population crash. In contrast, Laegreid et al (1983) observed higher cadmium toxicity during the growth sea-son, which they attributed to qualitative differences in DOC.…”
Section: Algal Biomass Doc and Ph Effects On Ionic Copper And Toxicitysupporting
confidence: 63%
“…One study of repeated copper additions to lake enclosures concluded that DOC, which increased in the spring with biological activity, was a seasonal controlling variable of copper effects (Winner et al 1990). Laegreid et al (1983) also found seasonal variation in cadmium toxicity, which they attributed to qualitative changes in DOC. Another study by Wangersky et al (1989) found that as the phytoplankton community developed, copper speciation shifted from predominantly inorganic to organically complexed, even though no metals were added to their mesocosm system.…”
Section: Significance For Ecosystemsmentioning
confidence: 99%
“…Speciation was determined in a few studies, and some of these [3–5] support the assumption of nontoxic metal complexes with DOM. Other research [6–9], however, has shown greater than expected metal toxicity in the presence of DOM.…”
Section: Introductionmentioning
confidence: 91%
“…They have also been utilized as biomonitoring systems to determine the Ž toxicity threshold in the environment Bringmann and . Khun, 1980;Laegreld et al, 1983 . There are reports about the utilization of some species of the genus Chlorella growing in media containing heavy metals, for evaluating the metal toxicity, the microalgae tolerance and the metal removal. Available data from these experiments support the possibility of using microalgae …”
Section: Introductionmentioning
confidence: 99%